REKONSTRUKSI TANGGUNG JAWAB HUKUM DALAM SENGKETA MEDIS AKIBAT PELIMPAHAN WEWENANG TINDAKAN KEDOKTERAN KEPADA PERAWAT: PASCA UU KESEHATAN NO 17/ 2023 - Yudhi (LPPM Universitas Awal Bros, 2025)
The dynamics of health services demand strong doctor–nurse collaboration, which often involves the delegation of medical authority. Recent regulatory changes through Law Number 17 of 2023 and Government Regulation Number 28 of 2024 have created significant implications for the boundaries of legal liability, particularly within the grey areas between mandates and delegation. This study analyzes the shifting paradigm of legal responsibility in the delegation of medical authority and the validity of electronic medical instructions as evidence in medical disputes. This research employs a normative juridical method using a statute approach and case approach, relying on secondary data analyzed qualitatively. The findings, based on Government Regulation Number 28 of 2024, confirm that delegated authority transfers full legal responsibility to the receiving nurse, while under a mandate, liability remains with the physician. However, medical instructions delivered via messaging applications (such as WhatsApp) without integration into Electronic Medical Records (EMR) carry a high risk of being deemed legally invalid, placing nurses in a vulnerable position regarding malpractice claims. In remote and underserved areas (DTPK), legal protection becomes conditional, depending on urgency and the unavailability of medical personnel. Therefore, the formalization of rigid standard operating procedures (SOPs) regarding the validation of digital instructions within EMR systems is urgently required to ensure legal certainty for healthcare workers.